Approaches to adapting to impacts of climate change in northern Iran: The application of a Hydrogy-Economics model. (20th January 2021) - Kalbali, Elham; Ziaee, Saman; Najafabadi, Mostafa Mardani; Zakerinia, Mehdi
Abstract: Climate change imposes adverse effects on water resources and agriculture in different regions of the world including Iran, so farmers need better adaptation to this phenomenon in order to maintain a steady livelihood. The present study aimed to analyze the future of water resources and agricultural sector affected by climate change in the Qarah Su Basin in Golestan province, Iran. The results indicate that the mean temperature will rise by 3.5 °C and the mean precipitation will decrease by 0.6 mm over the 2011–2040 period under the climate change scenario. Higher temperatures and lower rainfall in the hydrological sector will result in a decline in the river's runoff and consequently, a decline in the water allocated to the agricultural sector. The results of the economic model reveal that under climate change, crop acreages will decrease by 36% in Gorgan and 26% in Kordkuy and gross return will decrease by 10% and 8% versus the baseline year in these regions, respectively. The greatest decrease will happen for cotton due to its high water demand and low gross profit. But, no significant change will happen in its acreage in Bandar Torkman. To counteract the negative effects of climate change, the scenario of increasing irrigation efficiency and changing cropping type and pattern was applied. So, policymakers can use a combined model to mitigate the adverse impacts of climate change on the agricultural sector, thereby increasing the acreage of these crops in Gorgan and Kordkuy and improving the gross income of the agricultural sector in the three regions versus the climate change scenario. Highlights: A WEAP-ECONOMIC model was employed to analyses the impact of climate change on water resources in the Qarahsu Basin (Iran). Increased climate changes affect the cultivated areas and farming yields. Managerial strategies could be developed to increase irrigation efficiency, change the cultivation pattern.